Potential Climate Change Impacts on the Abiotic Degradation of Acyl-Homoserine Lactones in the Fluctuating Conditions of Marine Biofilms - Roggatz, Christina C.; Parsons, Daniel R. (Frontiers in Marine Science, 2022)
Marine biofilms are functional communities that shape habitats by providing a range of structural and functional services integral to coastal ecosystems. Impacts of climate change on biological aspects of such communities are increasingly studied, but impacts on the chemicals that mediate key interactions of biofilm organisms have largely been overlooked. Acyl-homoserine lactones (AHLs), crucial bacterial signals within biofilms, are known to degrade through pH and temperature-dependent hydrolysis. However, the impact of climate change on AHLs and thus on biofilm form and function is presently unknown. This study investigates the impact of changes in pH and temperature on the hydrolysis rate, half-life time and quantitative abundance of different AHLs on daily and seasonal timescales for current conditions and future climate change scenarios.We established the mathematical relationships between pH, hydrolysis rates/half-life times and temperature, which revealed that natural daily pH-driven changes within biofilms cause the greatest fluctuations in AHL concentration (up to 9-fold). Season-dependant temperature enhanced or reduced the observed daily dynamics, leading to higher winter and lower summer concentrations and caused a shift in timing of the highest and lowest AHL concentration by up to two hours. Simulated future conditions based on climate change projections caused an overall reduction of AHL degradation and led to higher AHL concentrations persisting for longer across both the daily and seasonal cycles.This study provides valuable quantitative insights into the theoretical natural dynamics of AHL concentrations. We highlight critical knowledge gaps on the scale of abiotic daily and seasonal fluctuations affecting estuarine and coastal biofilms and on the biofilms’ buffering capacity. Detailed experimental studies of daily and seasonal dynamics of AHL concentrations and assessment of the potential implications for a suite of more complex interactions are required. Substantial fluctuations like those we show in this study, particularly with regards to concentration and timing, will likely have far reaching implications for fundamental ecosystem processes and important ecosystem services such as larval settlement and coastal sediment stabilisation.